1997
DOI: 10.1093/humrep/12.10.2292
|View full text |Cite
|
Sign up to set email alerts
|

Serum levels of folate and cobalamin in women with recurrent spontaneous abortion

Abstract: We evaluated the folate and cobalamin status in 29 non-pregnant women with a history of recurrent spontaneous abortion (three or more consecutive) of unknown aetiology in comparison to 29 healthy nulligravidae of similar reproductive age (controls). Serum concentrations of folate and cobalamin showed no significant differences between the two groups. No correlation between age and vitamin concentrations was found. In the study group there was a significant negative correlation of the number of previous abortio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
15
3

Year Published

2000
2000
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(19 citation statements)
references
References 22 publications
1
15
3
Order By: Relevance
“…This is in keeping with findings previously reported by other authors [20, 66 -68] and suggests that the MTHFR gene mutation does not represent an increased risk of RM in our geographical environment. Vitamin B12 does not seem to play a role in this sense in either the present or in previous studies [69,44] , however, there are others that do not confirm these results [31,70] . It is interesting to note that even though the mean level of RBC folate in the study group was normal and similar to that found in the control group, the percentage of patients with RBC folate concentrations below the normal range was significantly higher in the RM than in the control group.…”
Section: Discussioncontrasting
confidence: 85%
See 1 more Smart Citation
“…This is in keeping with findings previously reported by other authors [20, 66 -68] and suggests that the MTHFR gene mutation does not represent an increased risk of RM in our geographical environment. Vitamin B12 does not seem to play a role in this sense in either the present or in previous studies [69,44] , however, there are others that do not confirm these results [31,70] . It is interesting to note that even though the mean level of RBC folate in the study group was normal and similar to that found in the control group, the percentage of patients with RBC folate concentrations below the normal range was significantly higher in the RM than in the control group.…”
Section: Discussioncontrasting
confidence: 85%
“…Some studies have reported an association between folate deficiency and increased risk of both spontaneous miscarriage [69,72,73] and RM [44] . In this respect, a previous study by George et al [74] is of note showing that compared with a control women group, patients with low folate levels were at increased risk of spontaneous miscarriage of fetuses with abnormal karyotype, whereas no significant association was observed with the risk of a normal fetal karyotype.…”
Section: Discussionmentioning
confidence: 99%
“…Folate deprivation has also been implicated in early pregnancy loss (Ronnenberg et al 2007) and recurrent spontaneous abortions (Sutterlin et al 1997, George et al 2002.…”
Section: Introductionmentioning
confidence: 99%
“…Recurrent miscarriage is usually defined as three consecutive first‐trimester miscarriages, and has been estimated to affect 1% of all women 3,4 . However, the definition of recurrent mis­carriage varies; some studies have included women with two consecutive miscarriages (‘repeated miscarriage’), 5–10 and the upper gestational limit has also varied to include up to 16 or 28 weeks of pregnancy 6,7 , 9–13 …”
Section: Introductionmentioning
confidence: 99%